Purification and Activity Testing of the Full-Length YycFGHI Proteins of Staphylococcus aureus - Türck, Michael; Bierbaum, Gabriele (PLOS ONE, 2012)
Background The YycFG two-component regulatory system (TCS) of Staphylococcus aureus represents the only essential TCS that is almost ubiquitously distributed in Gram-positive bacteria with a low G+C-content. YycG (WalK/VicK) is a sensor histidine-kinase and YycF (WalR/VicR) is the cognate response regulator. Both proteins play an important role in the biosynthesis of the cell envelope and mutations in these proteins have been involved in development of vancomycin and daptomycin resistance. Methodology/Principal Findings Here we present high yield expression and purification of the full-length YycG and YycF proteins as well as of the auxiliary proteins YycH and YycI of Staphylococcus aureus. Activity tests of the YycG kinase and a mutated version, that harbours an Y306N exchange in its cytoplasmic PAS domain, in a detergent-micelle-model and a phosholipid-liposome-model showed kinase activity (autophosphorylation and phosphoryl group transfer to YycF) only in the presence of elevated concentrations of alkali salts. A direct comparison of the activity of the kinases in the liposome-model indicated a higher activity of the mutated YycG kinase. Further experiments indicated that YycG responds to fluidity changes in its microenvironment. Conclusions/Significance The combination of high yield expression, purification and activity testing of membrane and membrane-associated proteins provides an excellent experimental basis for further protein-protein interaction studies and for identification of all signals received by the YycFGHI system.